IN THE MUSEUM - Ryan, A.J.; Gosling, A. (Akroterion, 2012)
Thanks to a generous donation by Ms. Joan Law, the Museum of Classical Archaeology has been able to purchase five Roman coins. Each of the coins illustrates an interesting aspect of Imperial culture and may be used to illustrate various aspects of Roman history. Furthermore, although the extent to which the iconography on coinage was under direct imperial control is debatable, a comparison with current imperial iconography and sentiment can be illuminating in assessing the public image of the emperor.